PEMBERDAYAAN SUBAK MELALUI “GREEN TOURISM” MENDUKUNG KEBERLANJUTAN PEMBANGUNAN PERTANIAN DI BALI - NI MADE SUYASTIRI YP (Universitas Sebelas Maret, 2012)
The rapid development of tourism have an impact on the declining interest of young people working in farming and followed with the increasing conversion of farmland to non agriculture. Beside that, the contribution of agricultural sector' to GDP tends to decrease. This condition results in the preservation and the existing of subak, because it is not possible to keep the existing of subak without the sufficient agricultural field. In addition, preservation for sustainable agricultural development is not possible without keeping the existing of subak.